Innovative Improvement Towards Sustainability And Growth In A Military Institute Of Higher Learning: The Case Of Universiti Pertahanan Nasional Malaysia - Mohd Fadhzil Bin Zainol
A military based educational institution is essential to the country’s development especially in the aspect of defence and security. Managing such institution has its own challenges. As the youngest public university, there are many challenges and obstacles that need to be addressed in order for UPNM to remain relevant, sustainable and thrive like other public universities. The overall scope of this study is confined within the organisation’s activities based on five areas and segments namely Management, Finance, Operations Management, Marketing, and Strategic Management. The objectives of this study is to determine issues faced by the organisation based on the five aforementioned areas and provide appropriate practical recommendations to the organisation. Case studies are used for this study and applied research was chosen as the research methodology. This study uses Quantitative research with questionnaire and secondary data used as tools in this research. Within the given time frame, four functional diagnostics and one strategic area have been identified to provide the diagnostic analysis needed. The implication of this study include: i) to assist the organisation to grow faster and emerge as an excellent educational institution, ii) cost saving for the university, iii) determine issues and propose practical solutions. The impact or outcome of this diagnostic analysis from the study is that UPNM is expected to apply a new set of assessment for recruitment and selection process for non-academic staff (Case 1), strengthen the operation process of human resource data management system (Case 2), Cost Effective Expenditure for Contract Staff Emolument (Case 3), utilising social media tools as marketing platform to enhance student enrolment (Case 4), provide proper human resource strategic plan for training and development (Case 5)